2001
DOI: 10.3133/ofr00196
|View full text |Cite
|
Sign up to set email alerts
|

Testing and application of diffusion samplers to identify temporal trends in volatile-organic compounds

Abstract: Methods for groundwater sampling have evolved over time. This evolution has been driven by changing theories on how to obtain representative aquifer water samples. Passive sampling is a fairly recent method that relies on the natural flushing capacity of a well to obtain representative samples. The use of diffusion samplers is one method of passive sampling and works well under certain conditions. As part of a 2-year study to determine the temporal variability and trends in concentrations of volatile organic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…To better quantify hydrologic conditions for the periods shown in figures 4 and 5, water levels were evaluated based on water-level statistics from long-term (from 1962) monitoring well MI-18 in OU2 ( fig. 1) Precipitation effects on ground water in OU1 were exam ined in Brayton and Harte (2001). Findings from that study showed that the land-surface crown inside the barrier area decreases infiltration of precipitation and recharge to ground water.…”
Section: Hydrogeologic Responsesmentioning
confidence: 99%
See 4 more Smart Citations
“…To better quantify hydrologic conditions for the periods shown in figures 4 and 5, water levels were evaluated based on water-level statistics from long-term (from 1962) monitoring well MI-18 in OU2 ( fig. 1) Precipitation effects on ground water in OU1 were exam ined in Brayton and Harte (2001). Findings from that study showed that the land-surface crown inside the barrier area decreases infiltration of precipitation and recharge to ground water.…”
Section: Hydrogeologic Responsesmentioning
confidence: 99%
“…Brayton and Harte (2001) found that recharge rates inside the barrier area decreased by as much as a half from pre-construction periods because of the addition of a semiconical land-surface crown during barrier construc tion. Analysis of additional data subsequent to that reported in Brayton and Harte (2001) indicates that a recharge rate of 2.45 gal/min also may be appropriate (about a 30-percent reduction from outside the barrier). Therefore, simulated ranges in direct recharge varied from 1.75 to 2.45 gal/min.…”
Section: Simulation Of the Remedial System And Its Operationmentioning
confidence: 99%
See 3 more Smart Citations